Sosialisasi Pembinaan dan Supervisi Kurikulum Merdeka Belajar - Muhammad Yuliansyah; Kasypul Anwar; Jarkawi Jarkawi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Science is increasingly developing from time to time. The development of this science supports the creation of new technologies that mark the progress of the times. Until now, the developing technology has entered the digital stage. Including in Indonesia, every field has begun to utilize technology to facilitate work, including in the field of education. As an entity related to human culture and civilization, education in various parts of the world has experienced very fundamental changes in the era of globalization.